Les dames bourgeoises dans le Paris du péché sans faute. La corruption de la dévotion chrétienne dans l’œuvre prévostienne - Luengo López, Jordi (Thélème. Revista Complutense de Estudios Franceses, 2022)
The aim of this study is to analyse how Marcel Prévost (1862-1941), a writer described as an “erotic Christian”, depicted the varied way in which women understood religion. In his works, a number of bourgeois ladies satisfied their libidinous desire in the confessional itself; an equal number went to Church to be forgiven for their sins, thus allowing them, in the manner of modern Aphrodites, to transgress once again. His writing also depicted the way in which the corruption of some nuns contradicted the strong Christian morality of certain prostitutes. A whole series of behavioural divergences that were the hallmark of Marcel Prévost’s writing, which showed that the idealised notion of the angel in the home was nothing more than a fantasy, far removed from the reality of Parisian society as he knew it.
Keywords: Marcel Prévost; Bourgeois young ladies; Christian devotion; Sin; Eroticism